2017
DOI: 10.1364/optica.4.000280
|View full text |Cite
|
Sign up to set email alerts
|

Focusing light inside dynamic scattering media with millisecond digital optical phase conjugation

Abstract: Wavefront shaping based on digital optical phase conjugation (DOPC) focuses light through or inside scattering media, but the low speed of DOPC prevents it from being applied to thick, living biological tissue. Although a fast DOPC approach was recently developed, the reported single-shot wavefront measurement method does not work when the goal is to focus light inside, instead of through, highly scattering media. Here, using a ferroelectric liquid crystal based spatial light modulator, we develop a simpler bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 59 publications
(112 reference statements)
2
147
0
Order By: Relevance
“…An improvement roadmap, mainly including the use of a faster wavefront modulator, onboard data acquisition, parallel processing, and more efficient optimization algorithm, has been detailed in the literature 61 and will not be reiterated here. For time-reversed wavefront shaping, the optical focusing optimization speed can already be completed within several milliseconds, 67,75,76 and the biggest obstacles toward in vivo are probably guidestar perturbation or modulation efficiency 83 and the complexity of the system. 74 Owing to the former factor, the peak-to-background ratio of an optical focus within scattering media is usually lower than 500, which quite often is insufficient for many applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An improvement roadmap, mainly including the use of a faster wavefront modulator, onboard data acquisition, parallel processing, and more efficient optimization algorithm, has been detailed in the literature 61 and will not be reiterated here. For time-reversed wavefront shaping, the optical focusing optimization speed can already be completed within several milliseconds, 67,75,76 and the biggest obstacles toward in vivo are probably guidestar perturbation or modulation efficiency 83 and the complexity of the system. 74 Owing to the former factor, the peak-to-background ratio of an optical focus within scattering media is usually lower than 500, which quite often is insufficient for many applications.…”
Section: Discussionmentioning
confidence: 99%
“…Within a complete time-reversed operation cycle, the phase pattern on the SLM needs to be refreshed only once. Optical focusing within several milliseconds has been demonstrated using this method, 75,76 opening hopes toward in vivo applications.…”
Section: Guidedstar-assisted Wavefront Shaping-based Optical Focmentioning
confidence: 99%
“…As TRUE focusing moves to deeper penetration depths, the amount of light which passes through the ultrasound focus decreases, in turn reducing the amount of ultrasound modulated light which is detected by the DOPC system. While recent work has shown that DOPC systems can operate even at very low light levels 21 , the signal-to-noise ratio still limits the ultimate depths accessible with the TRUE focusing system 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, traditionally scattering events have been regarded as an obstacle, and the speckle patterns generated by the coherent light propagation in tissue has been seen as one of the major noise sources in biomedical optical imaging [77,78]. However, recently, pioneering scientists have begun to explore the feasibility of exploiting scattering and the corresponding speckle patterns based on their deterministic feature within the medium's temporal correlation window [40,[63][64][65].…”
Section: Light Scattering In Complex Media and The Memory Effectmentioning
confidence: 99%
“…However, recently, researchers began to notice that the seemingly random scattering events and the resultant speckles are actually deterministic within a certain temporal window [37,38], and it is possible to reverse [39][40][41] or compensate for [42] the scattering-induced phase scrambling. To do so, researchers have developed several wavefront shaping (sometimes also referred to wavefront engineering) techniques, such as iterative wavefront optimization [23][24][25][26]28,[42][43][44][45][46][47][48][49][50][51], measuring the transmission matrix of the scattering medium [21,22,[52][53][54][55][56], and optical time reversal via phase conjugation [39,40,[57][58][59][60][61][62][63][64][65]. Nevertheless, the goals of these implementations are identical, i.e., to make light wavelets traveling along different optical paths interfere coherently at a region of interest (ROI) and form a bright optical spot (focus) out of the much darker background.…”
Section: Introductionmentioning
confidence: 99%